2000
DOI: 10.1177/004947550003000412
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in Swaziland: A Health Needs Assessment in Preparation for a Community-Based Programme

Abstract: This study was undertaken to assess the healthcare needs of people with tuberculosis (TB) in the rural district of Lubombo in Swaziland, with a view to improving the delivery of healthcare services. Qualitative and quantitative methodologies were used to describe the knowledge, attitudes and behaviour of TB patients, the epidemiology of TB, and the strengths and weaknesses of the current TB control programme. The incidence of TB is rising rapidly in this rural region of Swaziland. Poor treatment completion rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
(1 reference statement)
0
5
1
Order By: Relevance
“…17,27,34 Furthermore, there is copious evidence to suggest that TB can accelerate the progression of HIV infection and thus reduce the chances of survival. 3,35 In the present study, the rate of morbidity was higher amongst patients included in group 1 (20.8%) compared to group 2 (6.3%), although the difference was not statistically signifi cant (P = 0.816). Interfering factors, such as the distribution of patients between the ADT and SAE programs, may have contributed to this result despite the similarity of the other parameters between the two groups.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…17,27,34 Furthermore, there is copious evidence to suggest that TB can accelerate the progression of HIV infection and thus reduce the chances of survival. 3,35 In the present study, the rate of morbidity was higher amongst patients included in group 1 (20.8%) compared to group 2 (6.3%), although the difference was not statistically signifi cant (P = 0.816). Interfering factors, such as the distribution of patients between the ADT and SAE programs, may have contributed to this result despite the similarity of the other parameters between the two groups.…”
Section: Discussioncontrasting
confidence: 58%
“…If all of these criteria are met, the control of TB is one of the most cost-effective health interventions. 3 However, the number of TB cases is increasing worldwide, and the HIV pandemic is considered to be one of its major causes. 4,5 In developed countries an increase in cases was due to coinfection with HIV, and paradoxically, the increase in longevity with the emergence of TB in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in our synthesis reported that patients stopped treatment because they felt better and thought that they were cured [23,24,39,40,45,47,49,51] or because their symptoms abated [47,52,53]. Some studies noted that patients who felt worse than before treatment [23,24,32] or saw no improvement in their condition [2224,46] might be more likely to interrupt treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Patients could “become tired” of taking medications [26,30,40,44,45], discontinuing because of the length of treatment [38,40,45,46], the number of tablets [24], or fear of painful injections or drugs [29,47], as noted by both providers and patients.…”
Section: Resultsmentioning
confidence: 99%
“…The trial was preceded by a health needs assessment that included analysis of routine data, observation of clinical practice and interviews with staff and patients. Swaziland has a rapidly rising TB case detection rate which reflects the increasing incidence and prevalence of HIV (Pushpananthan et al 2000). For the baseline year prior to the intervention, there were major omissions in the TB register.…”
Section: Methodsmentioning
confidence: 99%